Late‐onset AD risk mutation PICALMH458R prevents plaque generation in 5xFAD mice. (20th December 2022) - Gomez‐Arboledas, Angela; Tran, Kristine M; Javonillo, Dominic I; Phan, Jimmy; Milinkeviciute, Giedre; Da Cunha, Celia; Forner, Stefania; Kawauchi, Shimako; Tenner, Andrea J; LaFerla, Frank; MacGregor, Grant R; Green, Kim N
Abstract: Background: To understand the processes that drive late‐onset Alzheimer's Disease (AD), genome‐wide association studies (GWAS) have uncovered many risk loci. One of these is within the phosphatidylinositol‐binding clathrin assembly protein (PICALM) gene, and a coding mutation has been identified (H458R) which conveys increased risk. PICALM is a cytosolic protein involved in regulating the formation of the lattice during endocytosis. The role of PICALM in AD has not fully defined, however, there are several reports indicating that PICALM affects AD risk primarily by modulating the production, transportation, and clearance of Aβ. Method: We generated and crossed Picalm H465R mice with the 5xFAD mouse model of AD, generating 4 groups: wild‐type (WT), PICALM H458R homozygous (HO), 5xFAD, and 5xFAD/ PICALM H458R HO, where we named the mice based on the human variant. They were aged to 4 months and 12 months, when plaque loads are being established and plateaued, respectively. Coronal brain sections were immunolabeled with Thioflavin‐S to visualize dense‐core plaques in the hippocampus subiculum and cortex. Plasma neurofilament light chain (NfL), a surrogate measure of brain damage, and soluble and insoluble Aβ levels were measured via meso scale discovery (MSD) technology. Result: 5xFAD/ PICALM H458R mice exhibited significant reduction in plaque density in both brain regions compared to 5xFAD mice, as well as reductions in plaque volumes at 4‐month. However, at 12‐month, the opposite is observed with increased plaque density in 5xFAD/ PICALM H458R compared to 5xFAD but no change in plaque volume. Similar to the observed plaque load at 4‐month, hippocampal insoluble fractions of 5xFAD/ PICALM Plasma NfL levels reflected reduced brain damage at 4‐month in 5xFAD/ PICALM H458R and a rise to similar level as 5xFAD at 12‐month, consistent with the plaque load. Conclusion: The results indicate PICALM H458R variant induces age dependent effects on Ab accumulation in 5xFAD mice, with an initial suppression of plaque genesis but ultimately leading to a higher plaque burden with age